(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The aim of this paper is to offer an overview of the use of the Latin alphabet to write the so-called fragmentary languages of Italy and Western Europe during Antiquity. The Latin alphabet was created from an Etruscan model to write Latin, but was also used to record texts in other languages: Etruscan, Oscan, Umbrian, the minor Italic dialects, Faliscan, and Venetic in Italy; Gaulish in the Gauls and other provinces in the north of Europe; and, finally, Iberian, Celtiberian, and Lusitanian in the Iberian Peninsula. The use of the Latin alphabet to write the so-called fragmentary languages represents a step before complete Latinisation. Two models are proposed to explain how the use and/or adaptation of the Latin alphabet to write the local languages came about.